Kajian Tinjauan: Halal Promotional Language - Ariffin, Adlina (2021)
This is a Bahasa Melayu version of a written survey that was carried out to collect data for my research entitled "Developing a Model on Effective Promotion of Halal Concept to Increase Halal Awareness through Multi-Perspective Approaches for the Halal Food Industry".